Relationship between fraction of backscattered light and asymmetry parameter. (January 2016) - Horvath, H.; Kasahara, M.; Tohno, S.; Olmo, F.J.; Lyamani, H.; Alados-Arboledas, L.; Quirantes, A.; Cachorro, V.
Abstract: A set of 6500 angular scattering function data have been obtained at various locations of the world: Vienna (Austria), Kyoto (Japan), Granada (Spain) and Palencia (Spain). The aerosols in these locations were considerably different, ranging from continental, urban, maritime, to desert dust. The volume scattering function has been measured between 5° and 175°, the values for 0–5° and 175–180° have been obtained by extrapolation of the shape of the curve, thus the whole range of scattering angles was available for calculating the backscattered fraction and the asymmetry parameter of the aerosol. The majority of the data points suggest an unanimous relation between backscattering and asymmetry parameter. The location where sampling took place and the type of aerosol seems to be of minor importance. These data have been compared with results of calculations for spherical or ellipsoidal particles having a lognormal monomodal size distribution of various sizes as well as several approximations for the relationship asymmetry vs backscattering available from the literature. With one exception it appears that an unanimous relation, fairly independent of location and type of aerosol, has been found between asymmetry parameters and backscattering ratio. The assumption of spherical particles seems to be a good assumption. Only for aerosols dominated by coarse mode particles the data points fall outside of the general trend, but again Mie calculations for spherical particles explain the behaviour. Highlights: The relation between backscattering and asymmetry has been investigated. Relationship can be simply approximated by spherical particles, slightly absorbing. Agreement with empirical relation and simple phase functions.